2019
DOI: 10.4081/ejtm.2019.7873
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intradermal Dexmedmotidine and subcutaneous Ketamine for post-surgical pain management in patients with abdominal hysterectomy

Abstract: Hysterectomy after cesarean section is the second most commonly used surgery for women in the United States. One of the most common problem after hysterectomy is pain. We decided to compare the effects of dexmedmotidine or ketamine on pain in patients by a double blind randomized clinical trial on 126 female candidates for abdominal hysterectomy in three groups of 42 persons referred to Taleghani hospital in Arak. For the first group, 50 micrograms of intradermal dexmedmotidine were injected, while in the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Our results were almost consistent with previous so that in a study conducted by Kamali et al, (2019) on 126 candidate patients for hysterectomy, they compared the effect of intradermal (subcutaneous) dexmedetomidine and ketamine in postoperative pain control. The results of mentioned study showed that both intradermal dexmedetomidine and subcutaneous ketamine have significant role in controlling postoperative pain in patients but the effect of ketamine was greater than dexmedetomidine (Kamali et al, 2019).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our results were almost consistent with previous so that in a study conducted by Kamali et al, (2019) on 126 candidate patients for hysterectomy, they compared the effect of intradermal (subcutaneous) dexmedetomidine and ketamine in postoperative pain control. The results of mentioned study showed that both intradermal dexmedetomidine and subcutaneous ketamine have significant role in controlling postoperative pain in patients but the effect of ketamine was greater than dexmedetomidine (Kamali et al, 2019).…”
Section: Resultssupporting
confidence: 91%
“…Our results were almost consistent with previous so that in a study conducted by Kamali et al, (2019) on 126 candidate patients for hysterectomy, they compared the effect of intradermal (subcutaneous) dexmedetomidine and ketamine in postoperative pain control. The results of mentioned study showed that both intradermal dexmedetomidine and subcutaneous ketamine have significant role in controlling postoperative pain in patients but the effect of ketamine was greater than dexmedetomidine (Kamali et al, 2019). The results obtained in this study were completely consistent with our findings because Based on the results achieved from the present study it was observed that the combination of intraperitoneal bupivacaine and magnesium sulfate was effective in controlling postoperative pain in patients with laparoscopic cholecystectomy as compared with intraperitoneal bupivacaine and intraperitoneal magnesium sulfate alone (Anand et al, 2014).…”
Section: Resultssupporting
confidence: 91%
“…Bleeding in late pregnancy is the cause of 40% of maternal mortality and 4-time increase in preterm delivery (1)(2)(3)(4). The main causes of bleeding in late pregnancy include placenta previa, preterm placental abruption, vein occlusion, and uterine rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Previous cesarean and uterine manipulations, history of miscarriage and curettage, multiparity, and older age are among the underlying factors of this disease (6). Initial manifestations of placenta previa are usually painless bleeding at the end of the second or third trimester of pregnancy and without any warning or uterine contraction (3). Preterm delivery, respiratory distress syndrome, anemia, low birth weight, low fifth-minute apgar, hospitalization in neonatal intensive care unit, need to mechanical ventilation and cerebral hemorrhage are neonatal consequences of placenta previa (7).…”
Section: Introductionmentioning
confidence: 99%